Evaluasi Work From Home Selama Masa Pandemi Covid-19 Di Kantor BPJS Ketenagakerjaan Mampang - Winda Wati; M. Khoirul Anwar (Universitas 17 Agustus 1945 Semarang, Indonesia, 2024)
Work From Home or working from home is the policy of the government of the Republic of Indonesia in handling cases of the spread of Covid-19 in Indonesia. The first Covid-19 case occurred in Indonesia in 2020, this made the Indonesian government create a large-scale social restriction policy which made all workers, both government and private, change their work system to Work From Home. BPJS Employment Mampang branch is a government agency that provides social security services to all workers in Indonesia. The aim of this research is to find out how work from home was evaluated during the Covid-19 pandemic at the BPJS Employment Mampang office. This research uses a qualitative approach and uses the CIPP model evaluation theory developed by Stufflebeam Zhang. The data collection techniques used were observation, interviews and documentation. The number of informants in this research was 12 informants. Data processing uses triangulation techniques. The results of this research show that the evaluation of Work From Home during the Covid-19 pandemic at the BPJS Employment Mampang office resulted in a fairly good evaluation. With the results of this evaluation, several employees agreed that the Work From Home program should continue to be implemented by making improvements to the Work From Home program so that it can be more effective for employees and the company. However, for employees who do not agree, it is because not all job desk jobs can be done Work From Home.